Swietenia mahagoni Leaves Extract: Antifungal, Insecticidal, and Phytochemical Analysis - Wael M. Khamis; Ahmed A. Heflish; Sarah El-Messeiry; Said I. Behiry; Abdulaziz A. Al-Askar; Yiming Su; Ahmed Abdelkhalek; Mohamed K. Gaber (Separations, 2023)
In this study, we investigated the antifungal properties of an acetone extract derived from the leaves of Swietenia mahagoni (SMAL) against two isolated fungi, Fusarium equiseti (OQ820153) and Rhizoctonia solani (OQ820152), from rice sheath. The extract was effective in inhibiting the growth of both fungi at the highest concentration tested, 3000 μg·mL−1. Laboratory tests on the LC20 of SMAL extract (49.86 mg·L−1) versus pyriproxyfen 10% EC (1.96 mg·L−1) were accomplished on Aphis gossypii Glover. The extract potently reduced the survival of the nymphs (49.58%) more than the other treatments. The longevity of nymphs treated with the extract had the highest prolongation at 9.67 days. The olfactory choice test exhibited the lowest aphid attraction percentage (23.33%). The HPLC of SMAL extract contained various phenolic compounds, and the most abundant found were catechin (752.64 µg·g−1), gallic acid, and chlorogenic acid, as well as flavonoids such as rutin (585.24 µg·g−1) and naringenin. A GC–MS analysis revealed n-hexadecanoic acid (37.1%) as the major compound, followed by oleic acid. These results suggest that SMAL extract has the potential to help plants fight against fungal and insect infections, making it a promising natural and renewable solution for long-term plant pest regulation.